Comparison of immediate postpartum contraception among women with a high versus low risk pregnancy in Mexico: a retrospective cohort study - Evelyn Fuentes-Rivera; Jacqueline Powell; Blair Darney (BMJ Open)
Objective We tested whether women who reported high-risk pregnancies or deliveries were more likely to receive immediate postpartum contraception prior to discharge compared with normal-risk women in Mexico.Methods This is a retrospective study using the National Health and Nutrition Survey. We classified women as high-risk based on reported complications in pregnancy and delivery. We used multivariable logistic regression to test the association of high-risk status and receipt of postpartum contraception (any modern method and Tier one methods) prior to discharge.Results Our sample included 5030 deliveries (population N=3 923 657). Overall, 19.1% of the sample were high risk. Over 60% of women in the high-risk and normal-risk group received immediate postpartum contraception, but a greater proportion of high-risk women received a method (67% vs 61% normal risk; p<0.001). However, in multivariable models, there were no significant differences in receipt of any modern method or tier 1 method by risk group.Conclusion Women with high-risk pregnancies were not more likely to receive postpartum contraception than the normal-risk group, once accounting for sociodemographic and clinical factors. Prenatal and postpartum contraception counselling should address the health effects of high-risk pregnancies and interpregnancy intervals to improve maternal health outcomes.